Reconstrução do ligamento patelofemoral medial para tratamento da luxação recidivante da patela - Gonçalves, Matheus Braga Jacques (2011)
OBJECTIVE: To present a new technique for reconstruction of the medial patellofemoral ligament (MPFL) in patients with recurrent patellar dislocation and to evaluate the clinical findings from this. METHODS: Between January 2007 and January 2008, 23 patients underwent reconstruction of the MPFL with a free graft from the semitendinosus tendon. After a minimum of 244 months of follow-up, 22 patients were evaluated using the Kujala and Lysholm clinical protocols. RESULTS: The mean follow up was 26.2 months. According to the Lysholm protocol, the patients had a mean score of 53.72 points preoperatively and 93.36 points postoperatively (p = 0.000006). According to the Kujala protocol, the mean score was 59.81 points preoperatively and 83.54 points postoperatively (p = 0.002173). CONCLUSION: Reconstruction of the medial patellofemoral ligament using the proposed technique showed excellent results over the short term, when evaluated by means of clinical protocols.